Pregnancy and Thyroid Dysfunction: Need for Universal Screening - A Pilot Study (Bangladesh Journal of Medical Science, 2013)
Aim: 1. To determine Thyroid dysfunction and antiTPO antibody status in pregnant women. 2. To know the benefit of LT4 therapy in maternal pregnancy outcome (antiTPO ab+ve vs antiTPO ab-ve groups) and 3. To determine the maternal and fetal outcomes in hypothyroid pregnant women and to decide whether universal screening of pregnant women for hypothyroidism is required or not. Materials and methods: A prospective study was done in mamata general hospital in the dept. of obg, over a period of 1 ½ years.105 antenatal women were included in the study. Outcome in these pregnancies were observed and analysed using appropriate statistical method. Results: There were only 3 patients with spontaneous abortions, 3 patients with pregnancy induced hypertention and only 1 patient had preterm delivery. There was more of thyroid dysfunction in anti TPO Ab +ve cases. But there was no significant adverse effect on pregnancy outcome in patients who were treated. Conclusion: Though our study included only a small number of antenatal women who were screened for thyroid abnormality since it was only a pilot study done in our hospital since our area is endemic for thyroid disorders due to iodine deficiency we recommend Universal screening to rule out thyroid dysfunction in pregnancy because the maternal and fetal complications can be reduced by early screening, diagnosing and correcting thyroid abnormality. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14173 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 49-52